2234. Implementing a Co-located HCV Clinic Within an HIV Clinic: Four Year Experience. (26th November 2018) - Villanueva, Merceditas; Rizk, Christina; Shiferaw, Bethel; Ogbuagu, Onyema; Malinis, Maricar; Miceli, Janet
Abstract: Background: Of the 1.2 M persons living with HIV in the United States, about 25% are co-infected with HCV. Even with the availability of highly effective direct antiviral agents (DAAs), the goal of HCV elimination requires improvements to the HCV treatment cascade, especially linkage to and initiation of treatment in underserved populations. We have implemented a co-located HCV clinic within our HIV clinic to circumvent barriers to HCV treatment. Methods: Between March 1, 2012 to April 30, 2017, all co-infected patients with chronic HCV infection (defined as positive HCV PCR) at Nathan Smith Clinic (HIV Clinic in New Haven, CT) were referred for consultation to the HCV co-infection clinic. This clinic was staffed by three physicians (additional HCV training), one physician assistant, one registered nurse and had access to a specialty pharmacy. Regular team meetings were held to review progress and treatment outcomes of patients who were initiated on DAAs. Relevant demographic, HIV and HCV parameters and clinic process data were abstracted and analyzed. Results: Of the 174 total co-infected patients, 85% were born between 1946 and 1964; 66% were males and 56% were African Americans. Comorbidities included: cirrhosis (67%); mental health problems (61%); active alcohol (31%); active substance use (56%). The majority ( n = 109, 63%) had HCV genotype 1. In terms of treatment cascade: 157 (90%) were referred to DAA prescriber, 140 (80%) were linked to DAA prescriber, and 102 (59%) started DAA therapy. Of the patients who started treatment, 84 (82%) had documented SVR12, 1 (1%) failed, 4 (4%) were awaiting SVR12 documentation, 7(7%) were on therapy, 4(4%) stopped therapy early, and 2 (2%) were lost to follow-up. There were no re-infections. After initial uptake in referrals and treatment initiation, a plateau was reached. Conclusion: Establishing a co-located HCV clinic within an HIV clinic has been successful in facilitating pre-treatment evaluation with overall SVR achieved in 48% of co-infected patients which compares favorably to published national HCV treatment cascades in mono-infected patients. Additional patient and provider barriers to completing clinic-wide HCV elimination are being analyzed. New approaches for promoting engagement in care are needed. Disclosures: All authors: No reported disclosures.